THE ROLE OF LEADERSHIP STYLE, WORK DISCIPLINE, AND COMPENSATION IN INFLUENCING EMPLOYEE PERFORMANCE MEDIATED BY WORK MOTIVATION WORK STUDY AT AGENCY "D" IN THE CITY OF SURAKARTA - Sulis Setiyanto; Nur Achmad (Ecopreneur.12, 2023)
The purpose of this study was to analyse the role of leadership style, work discipline, and compensation in influencing employee performance mediated by work motivation in the study of agency "D" in Surakata city. This study uses nonprobability sampling method, which is non-random sampling. In this study, the population is all employees who work at agency "D" with a total of 84 employees with details of 32 civil servants and 52 PPPK people. The sample taken in this study was 84 respondents. The technique that will be used in this research is the Structural Equation Model (SEM) analysis technique with Partial Least Square (PLS) statistics through the help of the SMART PLS application. Based on the research results previously described, the researcher can conclude that the variables of leadership style, compensation have a positive and significant effect on employee performance. Work discipline variables do not have a positive and significant effect on employee performance. Work motivation variables are not proven to mediate the effect of leadership style on employee performance. Work motivation variables are able to positively and significantly mediate the effect of work discipline on employee performance. Work motivation variable is able to positively and significantly mediate the effect of compensation on employee performance.